2016
DOI: 10.1182/blood-2015-12-685107
|View full text |Cite
|
Sign up to set email alerts
|

Use of hematopoietic cell transplants to achieve tolerance in patients with solid organ transplants

Abstract: The goals of tolerance in patients with solid organ transplants are to eliminate the lifelong need for immunosuppressive (IS) drugs and to prevent graft loss due to rejection or drug toxicity. Tolerance with complete withdrawal of IS drugs has been achieved in recipients of HLA-matched and mismatched living donor kidney transplants in 3 medical centers using hematopoietic cell transplants to establish mixed or complete chimerism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 67 publications
0
23
0
Order By: Relevance
“…Persistent chimerism for at least 6 months was associated with successful complete withdrawal of immunosuppression in 16 of 22 matched patients without rejection episodes or recurrence of primary renal disease in 5 year follow up [36][37][38][39]. Persistent mixed chimerism was achieved in some haplotype matched patients for at least 12 months by increasing the dose of T cells and CD34 + cells infused as compared to matched recipients in a dose escalation study.…”
Section: Total Lymphoid Elimination Protocolsmentioning
confidence: 96%
“…Persistent chimerism for at least 6 months was associated with successful complete withdrawal of immunosuppression in 16 of 22 matched patients without rejection episodes or recurrence of primary renal disease in 5 year follow up [36][37][38][39]. Persistent mixed chimerism was achieved in some haplotype matched patients for at least 12 months by increasing the dose of T cells and CD34 + cells infused as compared to matched recipients in a dose escalation study.…”
Section: Total Lymphoid Elimination Protocolsmentioning
confidence: 96%
“…Previous work has focused on combining solid organ and hematopoietic stem cell transplants. [8][9][10][11][12][13] However, with this approach only a minimal intensity conditioning regimen can be applied, most patients develop transient chimerism, and a proportion of patients need to be maintained on long-term immunosuppression.…”
Section: Sequential Kidney and Allogeneic Hematopoietic Stem Cell Tramentioning
confidence: 99%
“…17 In this setting, a more intense conditioning cannot be applied and most patients will reject the hematopoietic graft. 9,10,13 Although some patients may remain tolerant to the donor graft, rejection of hematopoietic cells might predispose to late chronic rejection of the solid organ, while administration of donor lymphocyte infusion (DLI) early after HSCT to convert to full donor chimerism is usually associated with a high incidence of GVHD. 17 Moreover, while mixed chimerism can be more likely obtained after HLA matched HSCT, in HLA mismatched transplantation there is a higher tendency to reject the donor cells.…”
Section: Sequential Kidney and Allogeneic Hematopoietic Stem Cell Tramentioning
confidence: 99%
“…None of the patients enrolled had kidney graft loss or GVHD with up to 14 years of observation (Scandling et al 2015). Strober (2016) reviewed a total of 41 HLA-matched and mismatched patients who were treated in three medical centers (MGH, Stanford University and Northwestern University) and who could be completely withdrawn from immunosuppressive drugs after combined kidney and HSCT transplantation and concluded that HSCT is a feasible approach leading to the complete withdrawal of immunosuppressive drugs from kidney transplant patients with follow-up periods of up to 10 years (median: 20 to 62 months). A prospective single-center study (Vanikar et al 2013) also reported that kidney transplantation by using HSCT in thymus, bone marrow and the portal and peripheral circulation safely and effectively prevents recurrent FSGS in patients with biopsy-proven primary FSGS.…”
Section: Therapeutic Potential Of Bmt For Recurrent Fsgsmentioning
confidence: 99%